Investigating the ecotoxicity of construction product eluates as multicomponent mixtures - Ines Heisterkamp; Stefan Gartiser; Ute Schoknecht; Oliver Happel; Ute Kalbe; Martina Kretzschmar; Outi Ilvonen (Environmental Sciences Europe, 2023)
Abstract Background The release of hazardous compounds from construction products can harm human health and the environment. To improve the sustainability of construction materials, the leaching of substances from construction products and their potential environmental impact should be assessed. Twenty-seven construction products from different product groups were examined with a combination of standardized leaching tests (dynamic surface leaching test and percolation test) and biotests (algae, daphnia, fish egg, luminescent bacteria, umu and Ames fluctuation tests). To identify the released substances, extensive qualitative and quantitative chemical analyses were performed, including gas chromatographic and liquid chromatographic screening techniques. Results Many of the tested eluates caused significant ecotoxic effects. Particularly high ecotoxicities were observed for grouts (lowest ineffective dilution (LID) up to 16384) and cork granules (LID up to 24578). The results of ecotoxicity tests allow the prioritization of the eluates that should be subjected to detailed chemical analyses. Organic screening by different methods and ranking the identified substances based on recorded hazard classification is a suitable approach to identify the relevant toxic substances. Conclusions Determining the ecotoxicity of eluates from construction products records the summary effect of all leachable substances. This instrument is especially useful for construction products of complex and largely unknown composition. The ecotoxicological and the chemical–analytical approach complement each other in an ideal way to characterize the potential hazard of eluates from construction products and to identify the environmentally hazardous components in these eluates. Our results confirm that the proposed harmonized methods for testing eluate toxicity are an adequate and applicable procedure to move toward a more sustainable way of building and to reduce toxic effects of construction products in their use phase in the environment..